ВИВЧЕННЯ ПРОБЛЕМИ ЦІННІСНОЇ КОМПЕТЕНТНОСТІ В УМОВАХ ВИЩОЇ ШКОЛИ (Педагогіка вищої та середньої школи, 2022)
The article deals with formation problem of the value competence under circumstances of higher school educational establishments. The analysis of the value competence as a notion has been given.